Enhancing interfacial charge transfer in a WO3/BiVO4 photoanode heterojunction through gallium and tungsten co-doping and a sulfur modified Bi2O3 interfacial layer. Issue 29 (16th July 2021) - Prasad, Umesh; Young, James L.; Johnson, Justin C.; McGott, Deborah L.; Gu, Hengfei; Garfunkel, Eric; Kannan, Arunachala M.
Abstract : Photoanodes containing a WO3 /BiVO4 heterojunction have demonstrated promising photoelectrochemical water splitting performance, but the ability to effectively passivate the WO3 /BiVO4 interface has limited charge transport and collection. Abstract : Photoanodes containing a WO3 /BiVO4 heterojunction have demonstrated promising photoelectrochemical water splitting performance, but the ability to effectively passivate the WO3 /BiVO4 interface has limited charge transport and collection. Here, the WO3 /BiVO4 interface is passivated with a sulfur-modified Bi2 O3 interfacial layer with a staggered band edge alignment to facilitate charge transfer and lifetime. Additionally, BiVO4 was co-doped with Ga 3+ at Bi 3+ sites and W 6+ at V 5+ sites ( i.e., (Ga, W):BiVO4 ) to improve the light absorption and photogenerated charge carrier concentration. The optimized WO3 /S:Bi2 O3 /(Ga, W):BiVO4 photoanode exhibited a photocurrent density of 4.0 ± 0.2 mA cm −2 compared to WO3 /(Ga, W):BiVO4 with 2.8 ± 0.12 mA cm −2 at 1.23 VRHE in K2 HPO4 under simulated AM 1.5G illumination. Time-resolved photoluminescence spectroscopic analysis of the WO3 /S:Bi2 O3 /(Ga, W):BiVO4 electrode validated the enhanced interfacial charge transfer kinetics. In operando femto- and nano-second transient absorption spectroscopy confirmed the presence of long-lived photogenerated charge carriers and revealed lower recombination initially due to rapid charge separation of WO3 /S:Bi2 O3 /(Ga, W):BiVO4 . The distribution and role of sulfur was further investigated using EDAX, XPS and TOF-SIMS depth profiling. Finally, a Co-Pi co-catalyst layer was added to achieve a photocurrent of 5.1 ± 0.25 mA cm −2 and corresponding H2 generation rate of 67.3 μmol h −1 cm −2 for the WO3 /S:Bi2 O3 /(Ga, W):BiVO4 /Co-Pi photoanode.